FROM DAWN TO DUSK:STORIES OF THE POSTGRADUATE LIFE VOLUME THREE - Asst. Prof. Dr. Venosha Ravana; Assoc. Prof. Dr. SARALA @ THULASI A/P PALPANADAN (Penerbit UTHM, 2025)
“From Dawn to Dusk: Stories of the Postgraduate Life (Volume 3)" is a compelling collection of personal narratives that delve into the daily lives of past and current postgraduate students. Extending from the first and second volumes which published 13 personal narratives collectively, this book also provides an intimate look at the journey of academia, offering readers a glimpse into the routines, challenges, triumphs, and reflections that define the postgraduate experience. Through a series of thoughtfully curated stories, this book captures the essence of what it means to pursue advanced studies, highlighting both the universal and unique aspects of academic life. This book is aimed at a broad audience, including current and prospective postgraduate students, educators, academic professionals, and anyone interested in the personal side of higher education. It appeals to those who are curious about the realities of postgraduate life and those seeking inspiration, guidance, or simply a sense of shared experience. The book has the potential to build a sense of community among postgraduate students and alumni. In short, this book is a big shoutout to postgraduate students who have survived and are surviving this magical journey from dawn to dusk.